Stratigraphy, paleoenvironmental evolution and regional significance of the Silurian Lake Aylmer-Lake Saint-Francois belt, Eastern Townships, Quebec - Lavoie, Denis; Bourque, Pierre-André (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1992)
Upper Silurian rocks outcrop in a relatively narrow belt centered on Lake Aylmer in the Eastern Townships of southern Quebec. Two distinct lithotectonic units form this belt. The Lac Aylmer Formation is a 1200 m-thick autochthonous unit, lying with disconformity over-the Middle-Upper Ordovician Magog Group. The Lac Lambton Formation is a 1100 m-thick unit unconformably overlying the Middle Ordovician or older Ascot Complex. The Lac-- - -Lambton Formation is part of an allochthonous succession, transported northwestward during the Acadian orogeny along the La Guadeloupe fault. The Lac Aylmer Formation comprises a lower conglomeratic member, a middle sandstone/siltstone member and an upper mixed fine-grained, siliciclastic carbonate member with local reefoid limestone masses. The Lac Lambton Formation is divided into eight informal members, collectively comprising conglomerates, carbonates and fine-grained siliciclastics. The upper parts of both formations have yielded Pridolian (Late Silurian) brachiopods. Field and petrographic studies of the various conglomerates have shown that they share a clast source (the Ascot Complex) but were deposited in dissimilar environments. The two formations were part of distinct depositional basins separated by an emergent topographic element, the Ascot Complex. The lack of detailed biostratigraphic data for most parts of the units raises the possibility that the basal disconformity/unconformity could be either Taconic (Late Ordovician) or Salinic (Late Silurian).